AKTIVITAS FISIK PADA PASIEN DIABETES MELITUS TIPE 2 DENGAN NEUROPATI PERIFER : TINJAUAN LITERATUR - Rima Novia Putri (Jurnal Keperawatan Abdurrab, 2019)
Type 2 diabetes mellitus is a chronic disease that could cause damage to foot peripheral nerves, namely peripheral neuropathy. Diabetic peripheral neuropathy is a damage and inability to regenerate nerve cells due to exposure of chronic hyperglycemia which can lead to various symptopms and complications. Therapy is aimed at improving symptoms and delaying development of peripheral neuropathy, one of which is physical activity which is one of the cornerstones of management of diabetes mellitus. An explanation of the benefits of physical activity in diabetes mellitus has been widely discussed, but nore in peripheral neuropathy. This literature review aims to explain the types and benefits of physical activity in peripheral neuropathy. Seven literature reviewed were obtained through electronic database search EBSCOHost, Proquest, and Clinical Key with key words physical activity, exercise intervention, diabetic peripheral neuropathy, and type 2 diabetes mellitus. Peripheral neuropathy patients can carry out various types of physical activity, either weight bearing or non-weight bearing exercise. Patients with ulcers, wounds and severe foot deformity can do non-weight bearing exercise such as static cycling and upper body ergometer. Another can do walking, aerobics, balance exercises, stretching, tai chi, resistance training, and foot ankle exercises. Aerobics is a physical activity that can prevent and delay development of peripheral neuropathy. Balance training can improve sensory and motor neuropathy. In general, physical activity can improve innervation in the cutaneous tissue, regenerate nerve cells, improve the symptoms of neuropathy in the form of pain, balance disorders, risk of falls, and obstacles to physical mobility.